“Distant Yet United”: The Redefinition of Actors, Actresses and Celebrities in the Italian Pandemic Television Scenario - Luca Antoniazzi; Luca Barra (Cinergie, 2022)
This paper investigates the television presence of Italian actors and actresses in the recent pandemic emergency. It draws on a wide range of published, online and video materials concerning both performers’ public discourse and television shows. Dealing with the relationship between actors and television, the article mainly focuses on three mutually influential processes that took place first in the lockdown and then in the months that followed. On one side, many peculiarities of television celebrity have characterized the public presence of actors and actresses of various artistic backgrounds. On another side, television space changed due to health and safety regulations, with studio audiences disappearing and then reappearing, making room for professionals and different forms of actorship. On yet another side, actors and actresses have redefined their relationship with the audience in public communication ads to raise awareness and provide information about the pandemic. At a time when domestic audiovisual consumption increases, not only does TV confirm its industrial and cultural role, but it also becomes a space of attraction for many celebrities and for other more marginal actors. The pandemic period is thus also a time of experimentation, in which multiple forms of actorship come into play on the small screen and partly redefine their characteristic features and the overall system of Italian celebrity.